PENEGAKAN HAK ASASI MANUSIA: Representasi Nilai Universalitas Islam yang Humanis - Suryani Suryani (Millah: Journal of Religious Studies, 2012)
This paper discusses the concept of human rights enforcement and humanist Islamic universal values. Islamic law is a set of religious rules that govern the behavior of the Muslims in all aspects, both individual and collective nature. Due to the comprehensive characteristic, Islamic law occupies an important position in the view of Muslims. Islam claims that the idea stemmed from the Medina Constitution or the Charter of Medina 624 AD. In Islamic perspective, human right is based on theocentric approach while the West uses anthropocentric approach. This difference often raises a controversy in seeing the same issue.